Chemical study on the leaves of Cyphostemma digitatum - Al- Mahweety, Jamal A. N. (PSM Biological Research, 2016)
Phytochemical study on the leaves of Cyphostemma digitatum obtained from Sana’a has been conducted. The separations of the chemical components were carried out by different chromatography techniques and their structures were elucidated by spectroscopic methods such as mass spectrometry (MS), 1H and 13C NMR and by comparison with those of previously reported data. Four compounds were isolated and identified as follows, triterpenes which was identified as Lupeol, Dioxo-urs-12-en-28-oic acid and Longistylin A, Piceid as a stilbenoid glucoside.